Increased PKMζ activity impedes lateral movement of GluA2-containing AMPA receptors. - Yu, N; Uhm, H; Shim, J; Choi, J; Bae, S; Sacktor, T; Hohng, S; Kaang, B (BioMed Central, 2017)
Protein kinase M zeta (PKMζ), a constitutively active, atypical protein kinase C isoform, maintains a high level of expression in the brain after the induction of learning and long-term potentiation (LTP). Further, its overexpression enhances long-term memory and LTP. Thus, multiple lines of evidence suggest a significant role for persistently elevated PKMζ levels in long-term memory. The molecular mechanisms of how synaptic properties are regulated by the increase in PKMζ, however, are still largely unknown. The α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor (AMPAR) mediates most of the fast glutamatergic synaptic transmission in the brain and is known to be critical for the expression of synaptic plasticity and memory. Importance of AMPAR trafficking has been implicated in PKMζ-mediated cellular processes, but the detailed mechanisms, particularly in terms of regulation of AMPAR lateral movement, are not well understood. In the current study, using a single-molecule live imaging technique, we report that the overexpression of PKMζ in hippocampal neurons immobilized GluA2-containing AMPARs, highlighting a potential novel mechanism by which PKMζ may regulate memory and synaptic plasticity.